2005
DOI: 10.2460/javma.2005.226.532
|View full text |Cite
|
Sign up to set email alerts
|

Compendium of measures to control Chlamydophila psittaci (formerly Chlamydia psittaci) infection among humans (psittacosis) and pet birds, 2005

Abstract: Psittacosis, also known as parrot fever and ornithosis, is a bacterial infection of humans that can cause severe pneumonia and other serious health problems. It is caused by Chlamydophila psittaci, formerly known as Chlamydia psittaci. From 1988 through 2003, 935 human cases of psittacosis were reported to the CDC and most resulted from exposure to infected pet birds, usually cockatiels, parakeets, parrots, and macaws. In birds, C. psittaci infection is referred to as avian chlamydiosis. Infected birds shed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 9 publications
1
125
0
7
Order By: Relevance
“…Psittacosis typically causes influenza-like symptoms, and the clinical presentation can range from mild respiratory infection to severe pneumonia and systemic illness. However, a recent study showed that less than 1 % of correctly treated patients died as a result of C. psittaci infection (Smith et al, 2005). Here, we describe two unusually severe cases with fatal outcomes, which occurred at two different poultry processing plants in Hungary.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Psittacosis typically causes influenza-like symptoms, and the clinical presentation can range from mild respiratory infection to severe pneumonia and systemic illness. However, a recent study showed that less than 1 % of correctly treated patients died as a result of C. psittaci infection (Smith et al, 2005). Here, we describe two unusually severe cases with fatal outcomes, which occurred at two different poultry processing plants in Hungary.…”
Section: Introductionmentioning
confidence: 90%
“…Poultry-processing-plant employees should be considered a high-risk group for human psittacosis infections because of the close contact with domestic fowl, followed by handling and processing of poultry plumage and meat (Smith et al, 2005). In Hungary, the south-eastern counties are the most affected areas, as the majority of processing plants are traditionally located in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the symptoms of disease (termed psittacosis) are variable, ranging from no clinical signs at all to severe systemic disease (Andersen and Vanrompay 2000). From 1988 though 2003, a total of 935 human cases of psittacosis were reported to the US Centers for Disease Control and Prevention (CDC) (Smith et al 2005). Due to inherent difficulties in the diagnosis of psittacosis, prevalence rates are probably underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…In birds, the course of infection can be rather mild but a mortality rate of 50% or even higher is not unusual 1 . Faecal and nasal excretions of diseased birds are the primary source of human infections [6,13,23]. However, apparent clinically healthy Psittaciformes also present a threat to human health, since many cockatoos, parrots, parakeets and lories never get rid of the bacterium once infected and most of them actually become Cp.…”
Section: Introductionmentioning
confidence: 99%